1971
DOI: 10.1002/apmc.1971.050150116
|View full text |Cite
|
Sign up to set email alerts
|

Über wäßrige Dispersionen von Polyoxymethylenen

Abstract: Polyoxymethylene lassen sich in Wasser dispergieren, wenn sie hydrophile Gruppen oder hydrophile Polymersequenzen eingebaut enthalten. Besonders leicht dispergierbar sind carboxylatgruppenhaltige Copolymere des Trioxans, die durch Verseifung der entsprechenden Estergruppen enthaltenden Polymeren hergestellt werden können. Der Einbau von Estergruppen in Polytrioxan ist durch Copolymerisation, durch Übertragungsreaktion oder durch Pfropfung leicht durchzuführen. Auch Polyoxymethylene mit längeren hydrophilen nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…19 Hermann et al prepared a POM copolymer of trioxane with 2-hydroxyacetic acid methyl ester and reported that it incorporated carboxylic derivatives in POM. 20 Such modified-polymers with various functional groups, as well as compatibilizers, have potential as further improvement of mechanical properties of the POM/TPU blends from the viewpoint of interfacial reaction between POM and TPU, but the reaction and properties of the modified-POM in the POM/TPU blends have not been investigated so far. Moreover, the POM copolymer, prepared by cationic polymerization, possesses a hydroxyl end-group on the polymer chain, 21 but the interfacial reaction of the hydroxyl end-group in the POM/TPU blends has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…19 Hermann et al prepared a POM copolymer of trioxane with 2-hydroxyacetic acid methyl ester and reported that it incorporated carboxylic derivatives in POM. 20 Such modified-polymers with various functional groups, as well as compatibilizers, have potential as further improvement of mechanical properties of the POM/TPU blends from the viewpoint of interfacial reaction between POM and TPU, but the reaction and properties of the modified-POM in the POM/TPU blends have not been investigated so far. Moreover, the POM copolymer, prepared by cationic polymerization, possesses a hydroxyl end-group on the polymer chain, 21 but the interfacial reaction of the hydroxyl end-group in the POM/TPU blends has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several modified‐POM samples have been prepared, containing a variety of reactive groups as side chain branches from the main polymer backbone and as terminal groups on the polymer chain 14–20. Wissbrun reported that the POM copolymer of trioxane with epichlorohydrin comonomer reacted with thioglycolate to give modified‐POM with carboxylic derivatives 19.…”
Section: Introductionmentioning
confidence: 99%
“…Wissbrun reported that the POM copolymer of trioxane with epichlorohydrin comonomer reacted with thioglycolate to give modified‐POM with carboxylic derivatives 19. Hermann et al prepared a POM copolymer of trioxane with 2‐hydroxyacetic acid methyl ester and reported that it incorporated carboxylic derivatives in POM 20. Such modified‐polymers with various functional groups, as well as compatibilizers, have potential as further improvement of mechanical properties of the POM/TPU blends from the viewpoint of interfacial reaction between POM and TPU, but the reaction and properties of the modified‐POM in the POM/TPU blends have not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…The results provide possibilities for further and comprehensive improvements in the compatibility with glass binders and, therefore, the mechanical properties of glass‐fiber‐filled POM. Additionally, several modified POM samples have been prepared containing a variety of reactive groups as side‐chain branches from the main polymer backbone and as terminal groups on the polymer chain 17–23. Wissbrun22 reported that a POM copolymer of TOX with epichlorohydrin as a comonomer reacted with thioglycolate to produce a modified POM with carboxylic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Wissbrun22 reported that a POM copolymer of TOX with epichlorohydrin as a comonomer reacted with thioglycolate to produce a modified POM with carboxylic derivatives. Hermann and Burg23 prepared a POM copolymer of TOX with HAA methyl ester and reported that it incorporated carboxylic derivatives into POM. Such a series of modified POMs with various functional groups also have the potential to further improve the performance of POM composites.…”
Section: Introductionmentioning
confidence: 99%